(untitled) (TAMADDUN NURI JURNALI, 2024)
this article analyzes the works of the Jadidists, who, exploring the activities of the Khorezm Jadids, created encyclopedias and monographs. The relevance of the ideas and proposals contained in their works is also emphasized.